Giriraja Spent Hen Meat Patties Prepared by Using Food Processor - Reddy, B. Ramachendra; Mandal, P. K.; Kasthuri, S.; Venugopal, S.; Pal , U. K. (Journal of Meat Science, 2019)
Processing of meat from spent hen to different value added products by comminution and emulsion formation opens the avenues for  its economic utilization. By using cheaper equipment like food processor we can produce meat products economically for small scale  business. Among the emulsion based products, chicken patties are one of the most acceptable value added comminuted meat products.  Hence, the present study was proposed to standardize procedure and the recipe to prepare patties using food processor. The standardi zation of procedure for the preparation of patties using food processor different running time (2, 3 and 4 minutes) was carried out. The  recipe of patties was standardized using different levels of meat (65, 70 and 75%) and oil (7, 10 and 13%). The patties prepared with  food processor by 3 minutes running time had significantly (P
Keywords: Spent hen meat patties; Food processor; Physico-chemical quality; Sensory quality